Pengaruh Online Reviews di Tripadvisor terhadap Minat Beli pada Hotel Zuri Express Jimbaran Bali - I Putu Bagus Rama Wira Saputra; Ni Made Suastini; Clearesta Adinda (TOBA: Journal of Tourism, Hospitality, and Destination, 2024)
This research aimed at investigate the decline in purchasing interest at the Zuri Express Jimbaran Bali Hotel in early 2024, primarily due to a decrease in visits to the hotel's website. The study uses data collection techniques such as documentation and questionnaires, including searches on Tripadvisor and other online review platforms. The analysis approach includes quantitative descriptive, classical assumption tests, multiple linear regression, F test, t test, and coefficient of determination. The findings reveal that purchase interest at the hotel is significantly influenced by review quality, consistency, quantity, and recency, with review quality, consistency, and quantity having a positive and significant effect. However, review recency does not significantly influence purchase interest. The study highlights the importance of online reviews in influencing consumer behavior and purchasing decisions.